PRODUKTIVITAS RUMPUT Panicum maximum YANG DIPUPUK DENGAN JENIS DAN DOSIS BIO SLURRY BERBEDA - Witariadi N.M.; N.N. Candraasih, K. (Udayana University, 2018)
This experiment to determine the productivity of Panicum maximum with different types and doses of bio slurry. The experiment was conducted in a greenhouse for 3 months. The design was complete Randomized Design (RAL), factorial pattern . The factor were firstly the types of bio slurry; these types consisted of cow dung bio slurry (BS) and pig manure bio slurry (BB). The second factors was bio slurry fertilizer dosage , which were as a control without any fertelizer (D0); fertilizer dosage of 10 tons / ha (D1); 20 tons / ha (D2); and 30 tons / ha (D3). Variables Observed include plant growth, production, and growth characteristics. The results showed that there was interaction between different types and dosage of bio slurry fertilizer on plant height variables, and total leaves of Panicum maximum cv. Trichoglume. Pig manure bio slurry at 30 tons/ha dose gave the best growth and production of Panicum maximum cv. Trichoglume. It can be concluded that both types of bio slurry were able to increase growth and production of the grass and in this study pig manure bioslurry (BB) with 30 tons/ha dosage gave the best result. Keywords: growth, production, panicum maximum, bio slurry